Home safe : a novel - Berg, Elizabeth (New York : Random House, 2009)
Recently widowed Helen Ames and her twenty-seven-year-old daughter Tessa discover that money has disappeared in several big withdrawals from the Ames' retirement savings. What Helen's husband did with all their money turns out to be provocative, revelatory--and leads Helen and her daughter to embark on new adventures, and change.
Keywords: Widows -- Fiction; Mothers and daughters -- Fiction; Parent and adult child -- Fiction; Psychological fiction; Domestic fiction